Analisis Alih Kode pada Novel 'Mondang Versus Jakarta' Karya Sinar Yunita - afriany, fany (Jurnal Pena Indonesia, 2024)
This study aims to describe the form of code switching and the causes of code switching in the novel Mondang Versus Jakarta by Sinar Yunita. This research Model is descriptive qualitative with data in the form of text quoted from the dialogue in the novel mondang versus Jakarta by Sinar Yunita. The results found in this study is, found 15 texts in the form of internal code switching between Indonesian to Batak language. And transfer the eksteren code from Indonesian to English. The causes of code switching in the novel Mondang Versus Jakarta by Sinar Yunita are mostly influenced by the presence of a common mother tongue among speakers, the batak language. In this study, researchers only limited the analysis to code-switching events only. Keywords: Sociolinguistic, code switching, Novel, Mondang Versus Jakarta